Evaluate the English language book which developed for the first grade average in the light of verbal communication skills - Al-Zahrani, Abdulaziz bin Mohammed Shahwan (Arab Journal for Sciences and Research Publishing, 2016)
The objective of the study was to assess the extent to which the first grade English language book reflects an average of verbal communication skills. The methodology of the study: The descriptive approach was followed by a content analysis. The researcher reviewed the relevant literature and previous studies and extracted a list of verbal communication skills and then evaluated the FULL BLAST English book for the first grade in the light of these skills. Results: The study developed a new list of oral communication skills in five areas: social interaction, information, opinions, needs, drafting. The study found deficiencies in the units of the book in general, especially the first book of the inclusion of many of the necessary skills that would be found to help complete the construction of the system of oral communication in English, in addition to the weakness of the distribution of these skills in a consistent and appropriate to the ability of students to absorb and benefit from them and showed the results The second book surpassed the first book in verbal communication skills in its four units.